Effect Of Regulations On The Appropriate Use Of Antibiotics - DR N. A. ALEYKUTTY; DR. B. JAYAKAR; DR. P.SURESH; DR.SANTHOSH M MATHEWS (International Journal of Pharma and Bio Sciences, 2011)
The study was conducted to evaluate the effect of restriction on the appropriateness of the antibiotic use. It was performed before and after the restricted use of antibiotics in all the hospitalized patients in the medical ward. The uses of all antibiotics were regulated and uses of certain antibiotics were restricted. It was observed that the appropriateness was increased after restriction. The culture based treatment also increased. The causes for inappropriate use also studied. All the important parameters showed significant reductions after the regulation.